Desktop Driving Simulator with Modular Vehicle Model and Scenario Specification - Karsolia, Arpit (My University, 2014)
Driving Simulators are one of the key tools to simulate and verify, interactions between vehicle & driver in a realistic as well as conditioned traffic environment. Real vehicle testing and pure simulation (using a driver model) are two alternative tools of collecting such information. Relevant data from real vehicle testing requires a high degree of repetition, man-power and is time-consuming, not to mention expensive. Advanced driver simulators are present in Sweden which provide, very realistic driver experience and perception. They simulate, very accurately, a real-time scenario in a holistic environment. But, in the modern world, vehicle & traffic situations have become so complex that the application and usefulness of driver simulators has moved beyond its usual definition. Thus, every experiment goes through an intricate, time consuming and thus expensive process of experimental design & development. The solution proposed in this thesis is to use a driving simulator which is portable and can simulate an experiment/scenario at an office level before moving to advanced simulators or real testing. The Desktop driving simulator would provide a platform to test a potential idea at a lesser scale and establish its functionality. This thesis will also study the modularity of the vehicle model for parameterization and simulate common vehicle manoeuvres to investigate model accuracy. However, results obtained will not be at par with analysis on advanced simulators, especially regarding driver perception and response but may provide an indication towards its behaviour and relevance.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering